An Early Warning Method of Unbalanced Power Battery Capacity Attenuation Based on ARIMA Model - KANG Zuchao; XIONG Gang; WANG Wenming; ZHONG Xiongwu; ZHOU Yanhui (Kongzhi Yu Xinxi Jishu)
Unbalanced attenuation of power battery capacity of green energy bus has a large impact on the service life of battery and driving safety. It is of important significance to study a timely warning algorithm of the unbalance of power battery capacity attenuation. Based on power battery charging data, this paper constructs charging capacity data of a specific voltage interval that can characterize the attenuation of overall capacity of battery cell as characteristic data, and uses on-board intelligent terminal to complete the characteristic data collection during the charging cycle of test vehicle. For the characteristic data with time series characteristics, an ARIMA time series model is used to extract and predict the characteristics of the data, so as to realize the early warning function of power battery capacity attenuation unbalance. Application results show that the standard error between prediction result by this method and real result is less than 0.6 A·h and generally around 0.2 A·h, which can foresee the attenuation of battery capacity in the next month and meet the practical needs.